Designers' guide to Eurocode 1 : actions on buildings : EN1991-1-1 and -1-3 to -1-7 - 496264 Gulvanessian, H.; Formichi, P.; Calgaro, J. A. (London : Thomas Telford, 2009)
Includes bibliographical references and index